A filter at the entrance of the Golgi that selects vesicles according to size and bulk lipid composition - Maud Magdeleine; Romain Gautier; Pierre Gounon; Hélène Barelli; Stefano Vanni; Bruno Antonny (eLife, 2016)
When small phosphatidylcholine liposomes are added to perforated cells, they bind preferentially to the Golgi suggesting an exceptional avidity of this organelle for curved membranes without stereospecific interactions. We show that the cis golgin GMAP-210 accounts for this property. First, the liposome tethering properties of the Golgi resembles that of the amphipathic lipid-packing sensor (ALPS) motif of GMAP-210: both preferred small (radius < 40 nm) liposomes made of monounsaturated but not saturated lipids. Second, reducing GMAP-210 levels or redirecting its ALPS motif to mitochondria decreased liposome capture by the Golgi. Extensive mutagenesis analysis suggests that GMAP-210 tethers authentic transport vesicles via the same mechanism whereby the ALPS motif senses lipid-packing defects at the vesicle surface through its regularly spaced hydrophobic residues. We conclude that the Golgi uses GMAP-210 as a filter to select transport vesicles according to their size and bulk lipid composition.